dsm2cli: An Observable Pipeline for Translating Network Intents into Multivendor CLI with Independent Semantic Assessment - Menezes, Jerônimo; Bitzki, Leonardo; Kreutz, Diego; Almeida, Gefte; Pohlmann, Marcio; Mansilha, Rodrigo (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2026: Anais Estendidos do XLIV Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2026.23256, 2026)
Network configuration in multivendor environments remains challenging due to semantic inconsistencies and limited observability in intent-to-CLI workflows. We present dsm2cli, an observable pipeline that translates structured intents into multivendor CLI with independent LLM-based semantic assessment. The approach separates translation from evaluation and produces artifacts such as traceability data, votes, verdicts, and telemetry under a unified contract, without targeting formal verification. Across six scenarios, four configurations, and 72 executions, results show that dsm2cli enables comparison of strategies, exposes semantic failures missed by generation-only workflows, and highlights trade-offs between robustness, cost, and latency.